Can you feel the spiders: haptic feedback on virtual reality - Bica, Gustavo Alexandre da Fonseca Madeira Lopes (2018)
Anxiety disorders are the most common mental health problem in the world and it affects, on daily basis, a vast number of people all around the world. Even though there are a high number of people suffering from phobia, only a small percentage ever seeks treatment, usually sufferers avoid the source of the problem, even if it is meaning of constrains in daily and social activities. Due to the development and creation of new technologies with the focus on healthcare growing rapidly and a number of studies proving that virtual reality can be just as effective as in vivo exposure, while providing a less stressful experience, these findings can contribute to reduce the high number of people that never seeks treatment. In previous works of our group, the Veracity, virtual reality was already applied in the context of arachnophobia, an example of specific phobias as a mean to provide an exposure without any physical sensorial interaction. In this dissertation, we want to extend the system with a virtual haptic response when touching spiders. Although the use of haptic response has been used and it is being used successfully in other areas, to our knowledge this is a novelty in the relation to other works in the phobia treatment. The haptic feedback has impact in virtual spider’s level of realism/interaction, by adding the touch to the visual sensation. Through haptic feedback, while improving the realism, we aimed at maintaining the virtual experience "safe" in the phobic user perspective in comparison to in vivo exposure. In this work, we integrated the haptic feedback within the Veracity loop and evaluate the impact in the response of users to this new add-on. As in the original system we still collect physiological response of the users such as ECG, HR, Video and 3D tracking of Virtual objects that were used to compare the responses with and without haptic feedback. The preliminary evaluation of the system suggest that this approach is interesting to pursue but still need a more comprehensive evaluation to assert its usefulness and impact within the phobic users of the haptic feedback.